Review of Peter Maxwell Davies: Gabrieli: Canzona, Two Piano Pieces, Points and Dances, Buxtehude: Cantana: Also Hat Gott Die Welt Geliebet, Tenebrae Super Gesualdo, Fool’s Fanfare, Renaissance Scottish Dances, Purcell: Fantasia Upon One Note, Three Organ - Roberts, David (Contact: A Journal for Contemporary Music (1971-1990), 1981)